Taxonomy and origin of reindeer - Røed, Knut H. (Rangifer, 2007)
Reindeer and caribou was probably the key species for the human immigration and colonization in the Arctic and sub-Arctic by the retreat of the ice in the last glacial period. The close connection between human and reindeer has contributed to great interest and variation in reindeer taxonomy and origin. Through the history several both species, subspecies and types of reindeer and caribou have been described. The early taxonomy of the species is marked by comparisons of individual specimen using traits as body size, skin colour or antler formations - characteristics known to be highly variable and subjected to environmental and nutritional level. During the mid 1900s the taxonomy was more based on variation of morphological traits among populations by analysing a large series of specimens representative of the various geographic populations and a consensus of classification of several subspecies, all belonging to the same species, evolved. During late 1900 the development of modern molecular techniques procured tools for revealing genetic structure of populations reflecting different origin and isolation rather than environmental influences. The genetic structure revealed a major genetic dichotomy between American woodland caribou on the one hand and all other types of reindeer and caribou on the other which gave evidence that the ancestors of present woodland caribou had survived and evolved in ice free refugium south to the glacier in North America and the ancestors of all other types of reindeer and caribou had evolved separated from these in refugium in Eurasia and Beringia. The ancestors of present reindeer in Scandinavia appear furthermore to have evolved from different populations separated during the last glaciation period and the colonization and origin of present wild and domestic reindeer will be discussed in this perspective. Taksonomi og opprinnelse til rein Abstract in Norwegian / Sammendrag: Rein og caribou har hatt stor betydning for det moderne menneskets utvikling og kolonisering av nordlige Eurasia og Amerika etter siste istid. Den nære sammenhengen mellom mennesker og rein har bidratt til stor interesse og variasjon i oppfatningen av reinens taksonomi og opprinnelse. Et utall av både arter, underarter og raser av rein er beskrevet opp gjennom historien. Tidlig taksonomi av rein bar preg av å være basert på enkeltobservasjoner og på morfologiske karakterer som kroppsstørrelse, pelsfarge og størrelse og form på gevir, karakterer som i stor grad påvirkes av miljø og næringsforhold. Først på midten av 1900 tallet ble taksonomien i større grad basert på ulike morfologiske trekk som viste variasjon mellom bestander av rein, og en fikk bl.a. en forståelse av at alle underarter og former av rein og caribou tilhørte samme art. Med utviklingen av den moderne molekylærbiologien på slutten av 1900-tallet fikk en tilgang til verktøy som avdekket genetiske strukturer som reflekterer ulik opprinnelse og utvikling mer enn miljømessig påvirkning. Den genetiske strukturen som ble avdekket, viste liten overensstemmelse med oppdelingen i underarter som var basert på morfologiske trekk. Molekylærgenetiske struktur viser et hovedskille mellom amerikansk woodland caribou på den ene siden og all annen rein og caribou på den andre siden, noe som reflekterer at forfedrene til woodland caribou levde og utviklet seg i isfrie områder sør for iskanten i Nord-Amerika, mens forfedrene til andre typer rein levde atskilt fra disse i isfrie områder i Eurasia og Beringia. Forfedrene til dagens rein i Fennoskandia syntes også å ha utviklet seg fra atskilte bestander av rein som kan føres tilbake til slutten av siste istid. Innvandring og opprinnelse til dagens vill- og tamrein i Fennoskandia vil bli belyst i dette perspektiv.